Stories from Calchaquí (NW Argentina): Circulation, Asymmetries, and Alternative Pathways - Lazzari, Marisa; Scattolin, Maria Cristina (European Association of Archaeologists, 2021)
European-led archaeological exploration and research varied enormously across the Americas in the late 19th Century and early 20th Century. The lesser known history of these engagements in NW Argentina (NWA) points at root problems that continue to affect international cooperation today. Besides some remarkable records that are still in use today, the collective activities of early European practitioners have impacted enormously on both local researchers and descendant communities’ ability to both understand and engage with the region’s pre-Columbian past. This complex legacy, characterised by systematic and unsystematic excavations, field diaries and notes, as well as extensive artefact collection and exportation practices of various calibres, was predicated on the alienation of living indigenous communities from their past. This epistemic violence erased, through the will of the camera, the pen, and the spade, the desires and expectations of those who, as hired field labourers and guides, fearfully complied with orders to exhume ancient bodies and artefacts. This steady stream of practices and discourses concealed native peoples behind their objects and shaped Argentina’s early scientific archaeology, setting the bases for its development throughout subsequent decades. From the perspective of the Calchaquí valleys region of NWA, we propose three themes to critically address this legacy: Early travellers; Object Lessons; and Roads and Habitats. The first theme examines the enduring impact of the words and actions of very different figures in the late 19th Century and early 20th Century. The second theme the strange relocation stories of two objects, exposing a system of hierarchical and asymmetric practices of heritage management and knowledge production, which continue to undermine contemporary collaboration. The third theme addresses cooperation and collaboration today, through the lens of our experience in the last 13 years, offering conceptual elements for more equitable, integrated, and sustainable international cooperation.